Advisory commissions and administrative reform the Western model in Japan - Elliott, James (1984)
The advisory commission model (ACM) has long been a popular administrative device used by governments in the West to implement administrative reform. Since 1981, the Japanese government has successfully used the ACM in a major effort to reform the public sector, adapting and improving its implementation to conform with traditional practices, values, but at the same time, it has also been modified to suit more the purpose of the existing elite, rather than the wider public. This suggests that the ACM may still fail to respond swiftly enough to the needs of Japan in the 21st century.
Keywords: Administrative reform -- Japan; Advisory Commission Model (ACM)